Reflections on neighbourhood decentralization in Tower Hamlets - Stoker, Gerry; Savtory, Tony D.U; Charters, Steve; Carlyle, Susan; Baine, Sean
The Tower Hamlets is an area with considerable economic and social problems. In 1986 the liberals won control of the London Borough of Tower Hamlets. They implemented a radical experiment in decentralized service delivery and decision-making. The article reflects on the successes and failures of the scheme as it ran until 1990. It is a shared belief that decentralization has improved the delivery of some services
Keywords: Politics; Policy; Decision Making; Decentralization